Preparation method of high-magnetic-permeability epoxy glass cloth laminated board

By combining high magnetic permeability materials with epoxy resin and using specific process steps to prepare epoxy glass cloth laminate, the problem of insufficient magnetic permeability in the prior art is solved, and a laminate with high magnetic permeability and good mechanical properties is achieved. Suitable for advanced electrical materials.

CN119502534APending Publication Date: 2025-02-25SUZHOU SUJUE ELECTRICIAN MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411493222.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The magnetic permeability of existing epoxy glass cloth laminates is difficult to meet the performance improvement needs of modern electronic components.

Method used

By combining a highly magnetically permeable material with an epoxy resin, a specific process step, such as reactor reaction, mixing, impregnation, coating, stacking and press-curing, is prepared with high magnetic permeability epoxy glass cloth laminate.

Benefits of technology

The prepared laminate has high magnetic permeability and good thermal mechanical properties, and can be applied to F and H grade electrical materials. It has simple process and low cost, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100612320000081
    Figure BDA0005100612320000081
  • Figure BDA0005100612320000091
    Figure BDA0005100612320000091
  • Figure BDA0005100612320000092
    Figure BDA0005100612320000092
Patent Text Reader

Abstract

The invention relates to a preparation method of a high-magnetic-permeability epoxy glass cloth laminated board, which comprises the following steps: adding epoxy resin, a curing agent and a solvent into a reaction kettle to react for 4-6 hours, cooling after the reaction is finished, and adding a catalyst to obtain an epoxy resin polymer; mixing a high-magnetic-conductivity material with an epoxy resin polymer to obtain a magnetic epoxy resin adhesive; injecting a magnetic epoxy resin adhesive into a slurry tank of a gluing machine, and dipping, coating and gluing the alkali-free glass cloth to obtain a magnetic epoxy gluing cloth; the magnetic epoxy upper adhesive tape is stacked and then placed into a pressing machine to be pressed and cured, and the high-magnetic-conductivity epoxy glass cloth laminated board is obtained; the high-magnetic-conductivity material comprises any one or a mixture of more of pure iron, a silicon steel sheet, an iron-aluminum alloy, a soft magnetic ferrite composite material and an iron-cobalt alloy. The method has the effect of improving the magnetic permeability of the glass cloth laminated board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrical insulation materials, and in particular to a method for preparing a high-permeability epoxy glass cloth laminate. Background Art

[0002] High-permeability materials are soft magnetic materials, offering advantages such as easy magnetization, high remanence, good magnetic permeability, and low coercivity. Epoxy resins are polymers containing two or more epoxy groups and composed of aliphatic, alicyclic, or aromatic segments as the backbone. When reacted with a curing agent, they form a three-dimensional network of thermosetting materials with excellent electrical and dielectric properties, making them suitable for a variety of applications. There are many types of epoxy resins, including glycidyl ethers, glycidyl esters, glycidyl amines, aliphatic epoxy compounds, alicyclic epoxy compounds, heterocyclic epoxy resins, and hybrid epoxy resins.

[0003] Epoxy resin polymers offer excellent bonding properties, high bond strength, and a wide bonding surface. They can bond to many metal and non-metal materials and are a key component of structural adhesives. Epoxy resin polymers also possess excellent insulation properties and a high glass transition temperature, resulting in excellent thermal stability and machinability. Epoxy resins contain a high concentration of curing agents, which undergo ring-opening addition polymerization of epoxy groups. This curing process produces no low-molecular-weight products, exhibits low cure shrinkage, and exhibits excellent acid and alkali resistance. They are widely used in the bonding and packaging of electronic components, as well as in printed circuit boards and electrical insulation materials.

[0004] With respect to the above-mentioned related technologies, the inventors believe that as the demand and performance requirements for electronic components continue to increase, the magnetic permeability of ordinary epoxy glass cloth laminates is difficult to meet current needs and therefore needs to be improved. Summary of the Invention

[0005] In order to improve the magnetic permeability of the laminate, the present application provides a method for preparing a high magnetic permeability epoxy glass cloth laminate.

[0006] The present application provides a method for preparing a high-permeability epoxy glass cloth laminate using the following technical solutions: A method for preparing a high-permeability epoxy glass cloth laminate comprises the following steps: S1. Add epoxy resin, curing agent and solvent into a reactor, react at 115-130° C. for 4-6 hours, cool to below 40° C. after the reaction, add catalyst to obtain epoxy resin polymer; S2, mixing the high magnetic permeability material and the epoxy resin polymer prepared in step S1 to obtain a magnetic epoxy resin adhesive; S3, injecting the magnetic epoxy resin adhesive into the slurry tank of the gluing machine, impregnating, coating and gluing the alkali-free glass cloth to obtain a magnetic epoxy gluing cloth with a gluing content of 30-42%; S4, stacking the magnetic epoxy adhesive tape and placing it in a press for pressing and curing to obtain a high-magnetic-permeability epoxy glass cloth laminate; The high magnetic permeability material includes any one or more mixtures of pure iron, silicon steel sheet, iron-aluminum alloy, soft ferrite composite material, and iron-cobalt alloy.

[0007] By adopting the above technical solution, the high magnetic permeability material is combined with the epoxy resin to prepare a laminate having high magnetic permeability, good thermal mechanical properties and the like, and can be applied to F and H grade electrical materials. The high magnetic permeability material includes a soft ferrite composite material, which has low coercive force and is a material with low remanence and high magnetic permeability, and can effectively improve the magnetic permeability of the prepared laminate. At the same time, the composite material has good stability, and the mechanical properties of the prepared laminate are further improved.

[0008] Preferably, the mass ratio of the epoxy resin, curing agent, solvent and catalyst is 1:(0.1-0.5):0.2:0.01.

[0009] By adopting the above technical solution, the mass ratio of the epoxy resin, curing agent, solvent and catalyst is preferably within the above range, which can further improve the stability of the prepared laminate.

[0010] Preferably, the mass ratio between the high magnetic permeability material and the epoxy resin is (3-12):1.

[0011] By adopting the above technical solution, the mass ratio between the high magnetic permeability material and the epoxy resin is preferably within the above range, which can further improve the stability of the prepared laminate.

[0012] Preferably, the high magnetic permeability material includes any one or more mixtures of pure iron, silicon steel sheet, iron-aluminum alloy, soft ferrite composite material, and iron-cobalt alloy.

[0013] Preferably, the soft magnetic ferrite comprises iron oxyhydroxide, iron nickel and aluminum silicon iron composite.

[0014] By adopting the above technical solution, the soft ferrite composite material is a composite material obtained by insulating and coating soft magnetic powder and pressing it under high pressure. It has good mechanical properties, high permeability and low loss. The iron-nickel alloy has high temperature resistance, high magnetic permeability and good corrosion resistance. It also has a low magnetostriction coefficient and a magnetocrystalline anisotropy coefficient close to zero, so it has lower hysteresis loss. Sendust also has good magnetic permeability. The combination of the three can further improve the comprehensive performance of the prepared soft ferromagnet.

[0015] Preferably, the soft ferrite is prepared by the following method: Iron nickel and ferric oxyhydroxide are mixed and added to ethanol, γ-aminopropyltriethoxysilane is added, ultrasonic washing and drying are performed to obtain a composite, stannous chloride dihydrate is mixed with anhydrous ethanol, and stirring is performed to obtain a stannous chloride solution, aluminum silicon ferrosilicon powder is added to the stannous chloride solution, and the mixture is dried while stirring to obtain an aluminum silicon ferrosilicon composite after drying, silicone resin is mixed with acetone, and the aluminum silicon ferrosilicon composite is added after stirring, and the mixture is dried after stirring and cooled to room temperature to obtain a preform, and zinc stearate is added to the preform, and the mixture is pressed and annealed after stirring to obtain a soft magnetic ferrite.

[0016] By adopting the above technical solution, after the particles of the composite are insulated and coated, the particles can be insulated from each other, thereby reducing the eddy current loss between the particles, further improving the magnetic permeability and stability of the laminate, and thus improving the magnetic durability of the laminate. During the annealing process, stannous chloride generates tin oxide, which undergoes a confined solid-state reaction with the Al atoms on the surface of the aluminum silicon iron, and finally forms a uniform and dense aluminum oxide coating in situ on the surface of the aluminum silicon iron to achieve effective point isolation. At the same time, the bonding performance with the body is enhanced, further improving the stability and magnetic permeability of the laminate.

[0017] Preferably, the mass ratio of the iron-nickel, aluminum-silicon-iron composite to the iron oxyhydroxide is (1.4-1.6):1.8:1.

[0018] By adopting the above technical solution, the mass ratio of iron oxyhydroxide, iron nickel and sendust is preferably within the above range, which can further improve the stability of the soft magnetic ferrite composite material.

[0019] Preferably, the mass ratio of stannous chloride dihydrate to aluminum silicon sendust powder is (0.006-0.008):1.

[0020] By adopting the above technical solution, the mass ratio between stannous chloride dihydrate and aluminum silicon sendust powder is preferably within the above range, which can further improve the stability of the modified aluminum silicon sendust powder.

[0021] Preferably, in step S4, the pressing and curing conditions are: initial preheating temperature 90-105° C., preheating time 1-2 h, curing temperature 150-190° C., and holding time 5-8 h.

[0022] By adopting the above technical solution, preferably pressing until the curing conditions are within the above range, the product quality of the prepared laminate can be further improved.

[0023] In summary, this application includes at least one of the following beneficial technical effects: 1. After combining the high magnetic permeability material with the epoxy resin, the laminate prepared has high magnetic permeability and good hot mechanical properties, and can be used for F and H grade electrical materials. At the same time, the preparation method of the present application is simple, low-cost, easy to operate, and uses a wide range of raw materials. It can be completed using general equipment, which is conducive to industrial production. The soft magnetic composite material added to the laminate system has low coercivity and good magnetic permeability, which can effectively improve the magnetic permeability of the laminate. At the same time, it has good stability and improves the mechanical properties of the laminate. 2. Iron oxyhydroxide, iron nickel and iron silicon aluminum are added to the soft magnetic composite material. All three have good magnetic permeability, and at the same time have heat resistance, mechanical properties and good corrosion resistance. After the three are compounded, they can synergistically improve the overall magnetic permeability of the soft magnetic composite material, thereby further improving the magnetic permeability of the laminate. 3. After the iron oxyhydroxide, iron nickel and sendust are insulated, the particles can be insulated from each other, thereby reducing the eddy current loss between the particles, thereby improving the magnetic durability of the laminate, and thus improving the overall performance of the laminate. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Example 1 Preparation of soft magnetic composite materials: 0.3 g of stannous chloride dihydrate was mixed with 100 g of anhydrous ethanol, and stirred at a speed of 600 r / min for 30 min to obtain a stannous chloride solution. 50 g of aluminum silicon iron powder was added to the stannous chloride solution prepared above, and stirred at a speed of 500 r / min for 30 min. The mixture was then dried at 80° C. and cooled to 25° C. after drying to obtain an aluminum silicon iron composite. γ-aminopropyltriethoxysilane was mixed with ethanol to obtain a mixed solution with a mass fraction of γ-aminopropyltriethoxysilane of 0.6%. 26.66 g of iron nickel and 19.05 g of hydroxyl oxidized Iron was mixed with 34.29 g of aluminum silicon iron composite and added to the above-mentioned mixed solution. After ultrasonication for 15 minutes, it was repeatedly washed with ethanol three times and dried in an oven at 100°C to obtain a preform. 5 g of silicone resin was added to 15 g of acetone, followed by the preform, and then 5 g of stearic acid was added. The mixture was stirred at a speed of 300 r / min for 15 minutes. After stirring, it was vacuum dried at 60°C for 1 hour. The dried powder was passed through a 500-mesh sieve and then added to a powder hydraulic press for pressing. It was then annealed in an annealing furnace at a temperature of 630°C for 1 hour to obtain a soft magnet composite material.

[0025] Preparation of high magnetic permeability material: 40g of soft magnet composite material, 15g of pure iron, 15g of steel silicon sheet, 15g of iron-aluminum alloy, and 15g of iron-cobalt alloy were mixed evenly, and then sieved to obtain a high magnetic permeability material with a particle size of 100-500 mesh.

[0026] Preparation of epoxy resin: Bisphenol A epoxy resin E-51, bisphenol A epoxy resin E-44, bisphenol A epoxy resin E-42, and bisphenol A epoxy resin E-20 are mixed in equal mass ratios to prepare the epoxy resin.

[0027] Preparation of curing agent: diethylenetriamine, triethylenetetramine, ethylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, and m-phenylenediamine are mixed in equal mass ratios to prepare the curing agent.

[0028] Preparation of solvent: Toluene and ethanol are mixed in equal mass ratios to prepare the solvent.

[0029] Preparation of epoxy glass cloth laminate: S1. Add 100 g of epoxy resin, 10 g of curing agent and 20 g of solvent to a reactor, react at 115° C. for 6 h, cool to below 40° C. after the reaction, and add 5 g of catalyst to obtain an epoxy resin polymer; S2. Mix 100 g of the high magnetic permeability material and 33.33 g of the epoxy resin polymer obtained in step S1 with a high-speed stirrer for 2 h to obtain a magnetic epoxy resin adhesive; S3, injecting magnetic epoxy resin adhesive into the slurry tank of the gluing machine equipment, using alkali-free glass fiber cloth as the base material, performing dipping coating and gluing on the alkali-free glass fiber cloth and hot pressing and baking to cure the shaped magnetic epoxy gluing tape, the gluing machine kiln temperature is 95-160 ° C, the speed is 2.5-8m / min, and the magnetic epoxy gluing tape with a glue content of 30% is obtained; S4. After stacking the magnetic epoxy adhesive tape, put it into a press for pressing and curing. Set the starting preheating temperature of pressing and curing to 90°C, the preheating time to 2 hours, the curing temperature to 150°C, and the insulation time to 8 hours. After the pressing and curing is completed, a high-permeability magnetic epoxy glass cloth laminate is obtained.

[0030] Example 2 Preparation of soft magnetic composite materials: 0.4 g of stannous chloride dihydrate was mixed with 100 g of anhydrous ethanol, and stirred at a speed of 600 r / min for 30 min to obtain a stannous chloride solution. 50 g of aluminum silicon iron powder was added to the stannous chloride solution prepared above, and stirred at a speed of 500 r / min for 30 min. The mixture was then dried at 80° C. and cooled to 25° C. after drying to obtain an aluminum silicon iron composite. γ-aminopropyltriethoxysilane was mixed with ethanol to obtain a mixed solution with a mass fraction of γ-aminopropyltriethoxysilane of 0.8%. 29.1 g of iron nickel and 18.18 g of ferric oxyhydroxide were added. After mixing with 32.72g of aluminum silicon iron composite, it was added to the above-mentioned mixed solution, ultrasonicated for 15 minutes, washed repeatedly with ethanol 3 times, and dried in an oven at 100°C to obtain a preform. 5g of silicone resin was added to 15g of acetone, followed by the preform, and then 5g of stearic acid was added. The mixture was stirred at a speed of 300r / min for 15 minutes. After stirring, it was vacuum dried at 60°C for 1h. The dried powder was passed through a 500-mesh sieve and then added to a powder hydraulic press for pressing. It was then annealed in an annealing furnace at 680°C for 1h to obtain a soft magnet composite material.

[0031] Preparation of high magnetic permeability material: 40g of soft magnet composite material, 15g of pure iron, 15g of steel silicon sheet, 15g of iron-aluminum alloy, and 15g of iron-cobalt alloy were mixed evenly, and then sieved to obtain a high magnetic permeability material with a particle size of 100-500 mesh.

[0032] Preparation of epoxy resin: o-cresol epoxy resin, glycidylamine epoxy resin, glycidyl ester epoxy resin, glycidyl ether epoxy resin, alicyclic epoxy resin are mixed in equal mass ratios to prepare the epoxy resin.

[0033] Preparation of curing agent: dicyandiamide, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride are mixed in equal mass ratios to prepare the curing agent.

[0034] Preparation of solvent: Acetone and n-butanol are mixed in equal mass ratios to prepare the solvent.

[0035] Preparation of epoxy glass cloth laminate: S1. Add 100 g of epoxy resin, 50 g of curing agent and 20 g of solvent to a reactor, react at 130° C. for 4 h, cool to below 40° C. after the reaction, and add 5 g of catalyst to obtain an epoxy resin polymer; S2. 100 g of the high magnetic permeability material and 8.33 g of the epoxy resin polymer obtained in step S1 were mixed in a high-speed stirrer for 2 h to obtain a magnetic epoxy resin adhesive; S3, injecting magnetic epoxy resin adhesive into the slurry tank of the gluing machine equipment, using alkali-free glass fiber cloth as the substrate, performing dipping coating and gluing on the alkali-free glass fiber cloth and hot pressing and baking to cure the obtained magnetic epoxy gluing tape, the gluing machine kiln temperature is 95-160 ° C, the speed is 2.5-8m / min, and the magnetic epoxy gluing tape with a glue content of 42% is obtained; S4. After stacking the magnetic epoxy adhesive tape, put it into a press for pressing and curing. Set the starting preheating temperature of pressing and curing to 105°C, the preheating time to 1h, the curing temperature to 190°C, and the insulation time to 5h. After the pressing and curing is completed, a high-permeability magnetic epoxy glass cloth laminate is obtained.

[0036] Example 3 Preparation of soft magnetic composite materials: 0.35 g of stannous chloride dihydrate was mixed with 100 g of anhydrous ethanol, and stirred at a speed of 600 r / min for 30 min to obtain a stannous chloride solution. 50 g of aluminum silicon iron powder was added to the stannous chloride solution prepared above, and stirred at a speed of 500 r / min for 30 min. The mixture was then dried at 80° C. and cooled to 25° C. after drying to obtain an aluminum silicon iron composite. γ-aminopropyltriethoxysilane was mixed with ethanol to obtain a mixed solution with a mass fraction of γ-aminopropyltriethoxysilane of 0.7%. 27.92 g of iron nickel and 18.6 g of hydroxyl oxidized Iron was mixed with 33.48 g of aluminum silicon iron composite and added to the above-mentioned mixed solution. After ultrasonication for 15 minutes, it was repeatedly washed with ethanol three times and dried in an oven at 100°C to obtain a preform. 5 g of silicone resin was added to 15 g of acetone, followed by the preform, and then 5 g of stearic acid was added. The mixture was stirred at a speed of 300 r / min for 15 minutes. After stirring, it was vacuum dried at 60°C for 1 hour. The dried powder was passed through a 500-mesh sieve and then added to a powder hydraulic press for pressing. It was then annealed in an annealing furnace at a temperature of 650°C for 1 hour to obtain a soft magnet composite material.

[0037] Preparation of high magnetic permeability material: 40g of soft magnet composite material, 15g of pure iron, 15g of steel silicon sheet, 15g of iron-aluminum alloy, and 15g of iron-cobalt alloy were mixed evenly, and then sieved to obtain a high magnetic permeability material with a particle size of 100-500 mesh.

[0038] Preparation of epoxy resin: bisphenol A epoxy resin E-12, bisphenol A epoxy resin E-06, bisphenol A epoxy resin E-03, hydrogenated bisphenol A epoxy resin, and aliphatic epoxy resin are mixed in equal mass proportions to prepare the epoxy resin.

[0039] Preparation of curing agent: Tung oil anhydride, pyromellitic anhydride, triethanolamine, 2,4,6-tris(dimethylaminomethyl)phenol, 2-methylimidazole, 2-ethyl-4-methylimidazole, boron amine complex are mixed in equal mass ratios to prepare the curing agent.

[0040] Preparation of solvent: dimethylformamide and ethanol are mixed in equal mass ratios to prepare the solvent.

[0041] Preparation of epoxy glass cloth laminate: S1. Add 100 g of epoxy resin, 30 g of curing agent and 20 g of solvent to a reactor, react at 122° C. for 5 h, cool to below 40° C. after the reaction, and add 5 g of catalyst to obtain an epoxy resin polymer; S2. Mix 100 g of the high magnetic permeability material with 13.33 g of the epoxy resin polymer obtained in step S1 by stirring in a high-speed stirrer for 2 h to obtain a magnetic epoxy resin adhesive; S3, injecting magnetic epoxy resin adhesive into the slurry tank of the gluing machine equipment, using alkali-free glass fiber cloth as the base material, performing dipping coating and gluing on the alkali-free glass fiber cloth and hot pressing and baking to cure the obtained magnetic epoxy gluing tape, the gluing machine kiln temperature is 95-160° C., the speed is 2.5-8 m / min, and the magnetic epoxy gluing tape with a glue content of 36% is obtained; S4. After stacking the magnetic epoxy adhesive tape, put it into a press for pressing and curing. Set the starting preheating temperature of pressing and curing to 98°C, the preheating time to 1.5h, the curing temperature to 170°C, and the insulation time to 6.5h. After the pressing and curing is completed, a high-permeability magnetic epoxy glass cloth laminate is obtained.

[0042] Example 4 Example 4 is based on Example 3. In Example 4, when preparing the soft magnet composite material, 21.06 g of iron-nickel, 37.89 g of aluminum silicon-iron composite, and 21.05 g of iron oxyhydroxide are used.

[0043] Example 5 Example 5 is based on Example 3. In Example 5, when preparing the soft magnet composite material, 33.32 g of iron-nickel, 30.01 g of aluminum silicon-iron composite, and 16.67 g of iron oxyhydroxide are used.

[0044] Example 6 Example 6 is based on Example 3. In Example 6, 0.15 g of stannous chloride dihydrate is used in preparing the aluminum silicon ferrosilicon composite.

[0045] Example 7 Example 7 is based on Example 3. In Example 7, 0.75 g of stannous chloride dihydrate is used in preparing the aluminum silicon ferrosilicon composite.

[0046] Example 8 Example 8 is based on Example 3. In Example 8, when preparing the soft magnetic composite material, the mass fraction of γ-aminopropyltriethoxysilane is 0.3%.

[0047] Example 9 Example 9 is based on Example 3. In Example 9, when preparing the soft magnet composite material, the mass fraction of γ-aminopropyltriethoxysilane is 1.5%. Example 10 Example 10 is based on Example 3. In Example 10, the annealing temperature is 550° C. when preparing the soft magnetic composite material.

[0048] Example 11 Example 11 is based on Example 3. In Example 11, the annealing temperature is 750°C when preparing the soft magnetic composite material.

[0049] Example 12 Example 12 is based on Example 3. In Example 12, when preparing the epoxy resin polymer, the content of the curing agent is 5 g.

[0050] Example 13 Example 13 is based on Example 3. In Example 13, when preparing the epoxy resin polymer, the content of the curing agent is 90 g.

[0051] Example 14 Example 14 is based on Example 3. In Example 14, the amount of epoxy resin polymer added in step S2 is 50 g.

[0052] Example 15 Example 15 is based on Example 3. In Example 15, the amount of epoxy resin polymer added in step S2 is 5 g.

[0053] Example 16 Example 16 is based on Example 3. In Example 16, when preparing the soft magnet composite material, the aluminum silicon sendust powder is not treated with stannous chloride.

[0054] Example 17 Example 17 is based on Example 3. In Example 17, when preparing the soft magnet composite material, only iron nickel, iron oxyhydroxide and aluminum silicon iron are physically mixed to prepare the composite material.

[0055] Example 18 Example 18 is based on Example 3. In Example 18, no iron or nickel is added when preparing the soft magnet composite material.

[0056] Example 19 Example 19 is based on Example 3. In Example 19, no aluminum silicon iron composite is added when preparing the soft magnet composite material.

[0057] Comparative Example 1 Comparative Example 1 is based on Example 3, and no soft magnetic material composite material is added in Comparative Example 1.

[0058] Performance testing The following performance tests were performed on the samples of Examples 1-19 and Comparative Example 1: (1) Density (g / cm 3 ) (2) The weight of the sample was measured at 25°C and 50% humidity, and then it was cooled to 25°C after 24 hours at 180°C and 50% humidity. The weight of the sample was re-measured and the weight loss rate was calculated. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1. (3) The weight of the sample was measured at 25°C and 50% humidity, and then immersed in water at 25°C for 24 hours. The sample was removed and dried, and the weight of the sample was re-measured and the water absorption rate was calculated. Each sample was tested three times, and the average value was taken. The test results were recorded in Table 1. (4) Test the longitudinal bending strength of the sample under normal conditions and at 150°C. Test each sample three times, take the average value, and fill in the test structure in Table 1; (5) Test the magnetic permeability when the magnetic flux density B = 0.3 Tesla and the average magnetic permeability when the magnetic field strength H = 50 Oe and 100 Oe, and fill in the test results in Table 1; (6) Test the magnetic induction intensity at 2000A / cm and 3000A / cm respectively, and fill in the test results in Table 1.

[0059] Table 1 Partial test results of samples of Examples 1-19 and Comparative Example 1 Table 2 Partial test results of samples of Examples 1-19 and Comparative Example 1 Data Analysis Combining Table 1 and Table 2, it can be seen that the epoxy glass cloth laminates prepared in Examples 1-3 have good stability, product performance, high conductivity, and good magnetic induction intensity.

[0060] In Examples 4 and 5, when preparing soft magnet composite materials, the mass ratios of the iron-nickel, aluminum-silicon-iron composite and ferric oxyhydroxide used are not within the range specified in this application. This may be because when the iron-nickel content is too little or too much, it will affect the mutual synergistic performance between the iron-nickel, aluminum-silicon-iron composite and ferric oxyhydroxide, so the performance of Examples 4 and 5 are both reduced.

[0061] In Examples 6 and 7, the stannous chloride dihydrate used in the preparation of aluminum silicon iron composites is not within the range specified in this application. This may be because stannous chloride dihydrate affects the particle size of the prepared aluminum silicon iron composite. When the particle size is too large or too small, it affects the stability of the system. Therefore, the performance of Examples 6 and 7 is reduced.

[0062] The amount of γ-aminopropyltriethoxysilane used in Example 8 and Example 9 is changed. When the amount of γ-aminopropyltriethoxysilane is too little, the modification effect on the powder in the soft magnet composite material is weak. When the amount of γ-aminopropyltriethoxysilane is too much, it affects the overall stability of the system. Therefore, the performance of Example 8 and Example 9 are both reduced.

[0063] The annealing temperature in Examples 10 and 11 was adjusted. When the annealing temperature was too low or too high, the overall stability of the system and the product properties were affected. Therefore, the various performances of Examples 10 and 11 were reduced.

[0064] When the content of the curing agent or the content of the epoxy resin polymer in the system is not within the range specified in the present application, the stability of the system and the product performance are affected, so the performance of Examples 12-15 are all reduced.

[0065] It is difficult for aluminum silicon iron that is not treated with stannous chloride to form an aluminum oxide coating layer on the surface, so it is difficult to achieve effective electrical isolation. It is also difficult to further enhance the bonding force with the substrate, so the performance of Example 16 is reduced.

[0066] In Example 17, only the iron nickel, ferric hydroxide and aluminum silicon iron composite are physically mixed, which makes it difficult to achieve chemical bonding and reduces stability, so the performance of Example 17 is reduced.

[0067] In both Example 18 and Example 19, only the two were combined to prepare a soft magnet composite material, the synergistic performance decreased, and it was difficult to form a stable structure, so the performance of Example 18 and Example 19 both decreased.

[0068] In Comparative Example 1, no soft magnetic material was added, and the performance of the sample without the addition of soft magnetic material was greatly reduced.

[0069] This specific embodiment is merely an explanation of the present application and does not limit the present application. Based on the above description, relevant personnel can make various changes and modifications without departing from the technical scope of the present application. The technical scope of the present application is not limited to the contents of the specification and must be determined according to the scope of the claims.

Claims

1. A method for preparing a high magnetic permeability epoxy glass cloth laminate, characterized in that: The steps include: S1, adding epoxy resin, curing agent and solvent into a reaction kettle, reacting at 115-130°C for 4-6h, cooling to below 40°C after the reaction, adding a catalyst, and obtaining an epoxy resin polymer; S2, mixing the high magnetic permeability material and the epoxy resin polymer prepared in step S1 to obtain a magnetic epoxy resin adhesive; S3, injecting the magnetic epoxy resin adhesive into the slurry tank of the gluing machine, impregnating, coating and gluing the alkali-free glass cloth to obtain a magnetic epoxy gluing cloth with a gluing content of 30-42%; S4, stacking the magnetic epoxy adhesive tape and placing it in a press for pressing and curing to obtain a high magnetic permeability epoxy glass cloth laminate; The high magnetic permeability material includes any one or more mixtures of pure iron, silicon steel sheet, iron-aluminum alloy, soft ferrite composite material, and iron-cobalt alloy.

2. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 1, characterized in that: The mass ratio of the epoxy resin, curing agent, solvent and catalyst is 1:(0.1-0.5):0.2:0.

01.

3. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 1, characterized in that: The mass ratio between the high magnetic permeability material and the epoxy resin is (3-12):

1.

4. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 1, characterized in that: The high magnetic permeability material includes any one or more mixtures of pure iron, silicon steel sheet, iron-aluminum alloy, soft ferrite composite material, and iron-cobalt alloy.

5. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 4, characterized in that: The soft ferrite comprises iron oxyhydroxide, iron nickel and aluminum silicon iron composite.

6. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 5, characterized in that: The soft ferrite is prepared by the following method: The nickel iron and hydroxy iron oxide are mixed and added to ethanol, γ-aminopropyl triethoxysilane is added, ultrasonic washing and drying are performed to obtain a composite, stannous chloride dihydrate is mixed with anhydrous ethanol, and a stannous chloride solution is obtained after stirring, aluminum silicon iron powder is added to the stannous chloride solution, and the mixture is dried while being stirred to obtain an aluminum silicon iron composite after drying, silicone resin is mixed with acetone, and the aluminum silicon iron composite is added after stirring, and the mixture is dried after stirring and cooled to room temperature to obtain a preform, and zinc stearate is added to the preform, and the mixture is pressed and annealed after being stirred to obtain a soft magnetic ferrite.

7. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 6, characterized in that: The mass ratio between the iron-nickel, aluminum-silicon-iron composite and the iron oxyhydroxide is (1.4-1.6):1.8:

1.

8. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 6, characterized in that: The mass ratio of the stannous chloride dihydrate to the aluminum silicon ferrosilicon powder is (0.006-0.008):

1.

9. The method for preparing a high magnetic permeability epoxy glass cloth laminate according to claim 1, characterized in that: In step S4, the pressing and curing conditions are: initial preheating temperature 90-105° C., preheating time 1-2 hours, curing temperature 150-190° C., and heat preservation time 5-8 hours.

Citation Information

Patent Citations

  • Laminated magnetic conducting plate and manufacturing method thereof

    CN102169744A

  • Compose magnetic material for bond-molded magnetic body and bond-molded magnetic body

    JP1995326508A